2011
DOI: 10.4049/jimmunol.1101721
|View full text |Cite
|
Sign up to set email alerts
|

Ly6G+ Neutrophils Are Dispensable for Defense against Systemic Listeria monocytogenes Infection

Abstract: Listeria monocytogenes is a facultative intracellular bacterium that causes systemic infections in immunocompromised hosts. Early recruitment of myeloid cells, including inflammatory monocytes and neutrophils, to sites of L. monocytogenes infection is essential for the control of infection and host survival. Because previous experimental studies used depleting or blocking antibodies that affected both inflammatory monocytes and neutrophils, the relative contributions of these cell populations to defense agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
95
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 41 publications
17
95
2
Order By: Relevance
“…Interestingly, sgp130Fc treatment caused a reduction of neutrophil accumulation in the spleen. Recent studies from Shi et al (46) and Carr et al (47) analyzed the role of neutrophils for the control of L. monocytogenes. In those studies, depletion of neutrophils had either no consequences (46) or only affected control of infection when relatively high doses of bacteria where applied (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, sgp130Fc treatment caused a reduction of neutrophil accumulation in the spleen. Recent studies from Shi et al (46) and Carr et al (47) analyzed the role of neutrophils for the control of L. monocytogenes. In those studies, depletion of neutrophils had either no consequences (46) or only affected control of infection when relatively high doses of bacteria where applied (47).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from Shi et al (46) and Carr et al (47) analyzed the role of neutrophils for the control of L. monocytogenes. In those studies, depletion of neutrophils had either no consequences (46) or only affected control of infection when relatively high doses of bacteria where applied (47). Under the latter conditions, depletion of neutrophils mainly impaired control of infection in the liver (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neutrophils are the immediate responders to any infection and injury (within few hours), monocytes are the key players in modulating the inflammation by producing cytokines, such as IL-1β, IL-6, TNF-α, as well as iNOS, and thus controlling the early phase of different infections [5,9,10,22,23] or injury [24]. Recent studies using CCR2 (-/-) mice or highly specific depletion strategies confirmed that monocytes, but not neutrophils, are important mediators in the control infections [9,22]. Furthermore, during certain microbial infection the Gr-1 hi CCR2 + monocytes can differentiate into TipDCs and produce TNF-α, iNOS [11,17,25,26] and favor the clearance of the ongoing infection (Fig.…”
Section: Infection and Injurymentioning
confidence: 99%
“…inoculated with L. monocytogenes. Shi et al (69) argued that neutrophils are dispensable for the control of L. monocytogenes infection, whereas Carr et al (16) and Edelson et al (70) showed that neutrophils are protective. Discrepancies between those studies likely result from distinct experimental approaches (61).…”
Section: Discussionmentioning
confidence: 99%